ОНОМАСТИКОН ПРОИЗВЕДЕНИЙ РУССКОГО ПОСТМОДЕРНИЗМА КАК ПРОЯВЛЕНИЕ НЕПЕРЕВОДИМОСТИ (НА МАТЕРИАЛЕ ПОВЕСТИ ВЛАДИМИРА СОРОКИНА ДЕНЬ ОПРИЧНИКА) - Paluch, Anna (Przegląd Rusycystyczny, 2017)
The article presents associative characteristics of anthroponyms selected from Vladimir Sorokin’s novel Day of Oprichnik and referring to Russian history. The national character of these names as well as their implicit meaning and hidden allusions easily recognizable to Russian readers are a major obstacle for translators which does not allow them to carry all associations of multilayer names into the translated text. In translation practice, there is no adequate strategy for translating such a category of names and certain significant components of a postmodern text. For that reason these anthroponyms can be classified as “untranslatable in translation”.